1972
DOI: 10.1126/science.175.4028.1335
|View full text |Cite
|
Sign up to set email alerts
|

Visual Spatial Illusions: A General Explanation

Abstract: Representation at the visual receptors of such properties of the object as its size, shape, orientation, and movement undergo considerable variation as the distance, bearing, posture, and motion of the observer, relative to the object, changes. However, despite these gross and frequent deformations of the image, perceived properties remain extraordinarily stable. Such constancy has obvious biological utility; the observer perceives his world according to its fixed physicalfeatures rather than in terms of its v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
60
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(63 citation statements)
references
References 43 publications
3
60
0
Order By: Relevance
“…This claim is controversial. On the one hand, Day (1972) suggested that the tilt induction effect, the Zöllner illusion, and the tilted room illusion of Asch and Witkin (1948) were all caused by the same mechanism. On the other hand, Howard proposed that although the Zöllner illusion and the tilt induction effect were caused by one mechanism, context illusions that involved large stimuli (the rod-and-frame effect and the tilted room illusion) were caused by a different mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This claim is controversial. On the one hand, Day (1972) suggested that the tilt induction effect, the Zöllner illusion, and the tilted room illusion of Asch and Witkin (1948) were all caused by the same mechanism. On the other hand, Howard proposed that although the Zöllner illusion and the tilt induction effect were caused by one mechanism, context illusions that involved large stimuli (the rod-and-frame effect and the tilted room illusion) were caused by a different mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The Zöllner illusion has long been considered an example of the tilt induction effect (Day, 1972;Howard, 1982, pp. 156-157).…”
mentioning
confidence: 99%
“…It was found that length estimates were significantly different between the horizontals of the Ponzo figure and control stimuli, but not between the texture figure and a context-free control. The results suggest that inappropriate constancy scaling plays a minor role at best in the perception of geometric illusions.One category of theory that attempts to explain the operation of geometric illusions assumes that the failure to equate physicaUy identical elements in two-dimensional displays may be attributed to inappropriate constancy scaling (Day, 1972; Gergory, 1963;Tausch, 1954). Such a theory explains the Ponzo illusion by proposing that the angular portion of the figure suggests depth in the manner of linear perspective, and so the more "distant" of the two lines is perceived as larger when both lines subtend equal visual angles.…”
mentioning
confidence: 99%
“…Although the effects produced by these several variants have not been quantitatively compared, there is a general agreement that the shaft or the corresponding interval in the ''outward'' figure always appears longer than its counterpart in the ''inward'' figure. As a result, there has been much controversy about the genesis of the Müller-Lyer effect (6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), which still has no generally accepted explanation (21,22).…”
mentioning
confidence: 99%